Pendampingan Pastoral Terhadap Mahasiswa Yang Terikat Kuasa Okultisme: Studi Kasus Mahasiswa STT Abdi Sabda - Saragih, Elfrida; Bukidz, Danny Philipe (Sekolah Tinggi Diakones HKBP, 2023)
Occultism is a belief in dark powers, spiritual forces outside of God's power. Some members of the community practice occultism, such as belief in the spirits of the dead, talismans believed to protect the body, and immunity skills passed down by ancestors, which cause their descendants to suffer from frequent manifestations and possessions by evil spirits. Some STT Abdi Sabda Medan students are still bound by occultism, affecting them physically, psychologically, and spiritually. Therefore, there is a need for counseling for healing and recovery from their occultism attachment. This paper examines the need for counseling through pastoral counseling theories. The author conducted qualitative research and gathered data by interviewing seven students who were previously bound by occultism and experienced manifestations. They were also served by the Abdi Sabda Medan deliverance ministry team. Of the seven students, five recovered completely, three of whom joined the deliverance team, two did not join, and one is not yet fully recovered, while another refused to release their occult attachment. The author also interviewed Jaharianson Saragih, the deliverance ministry team's mentor, to strengthen the field data. This study aimed to explore how pastoral counseling is conducted on STT Abdi Sabda Medan students bound by occultism.